FITOREMEDIASI COD DAN TSS MENGGUNAKAN TANAMAN ECENG GONDOK (Eichhornia Crassipess) DAN KIAMBANG (Salvinia Molesta) PADA LIMBAH LAUNDRY - Jubaidi, Jubaidi; Maulana, Ilham; Ihwan Saputra, Arie (Jurnal Sanitasi Profesional Indonesia, 2022)
Today many developing business activities related to clothes washing and ironing services or better known as laundry services. Laundry business is a business engaged in washing and ironing services. This business is widely available in various big cities in Indonesia. The presence of a laundry service business has positive impacts such as providing economic benefits for laundry managers, while negative impacts are in the form of toxic, excessive amounts of laundry waste can contaminate water bodies and cause eutrophication, namely water bodies become rich in dissolved nutrients, and reduce dissolved oxygen content, and the ability the carrying capacity of water bodies for aquatic biota (Raissa and Tangahu, 2017). This study aims to treat laundry wastewater using water hyacinth and kiambang plants to reduce COD and TSS levels in laundry wastewater. This type of research is Quasi Experiment with the Prettes – Posttes design. Water hyacinth and Kiambang plant media can reduce COD and TSS levels within 5, 10, 15 days and are carried out in the laboratory of the Bengkulu Ministry of Health Polytechnic. The results showed that the water hyacinth and kiambang plants reduced COD levels equally, namely 88.89% within 15 days, while the water hyacinth and kiambang plants reduced TSS levels by 17.12% and the highest 18.02% within 15 days. It is hoped that the community can add insight and apply that water hyacinth and kiambang can be used as a medium to reduce COD levels better than reducing TSS in wastewater so that they can meet water quality requirements before being discharged into water bodies.